Education in ancestral rhythms: Black experiential knowledge in Afro-Carnaval music in Belo Horizonte - Loiola dos Santos, Marcone; Neves da Silva, Natalino (Ephemera: Revista do Programa de Pós-Graduação em Artes Cênicas da Universidade Federal de Ouro Preto, 2025)
This article aims to highlight the knowledge and socio-affectivities that constitute the creativity present in the Afro-Carnaval music of the Bloco Afro Angola Janga, during the Belo Horizonte (BH) Carnaval. It highlights rhythm as a key element of Black Popular Education mobilized by the celebration. Qualitative and ethnographic in nature, the analysis is based on percepts and events gathered through participant observation during the bloco’s rehearsals and narrative interviews with two associate members. It was understood that the percussive musical atmosphere, articulated through intersubjectivity and the mythopoetics of the orixás, holds the potential to instigate political-cultural imaginaries as a practice of recreating ancestral African and Afro-Brazilian knowledges, expressed in sounds, dances, performances, sensibilities, and other forms of learning. Thus, this research contributes to the implementation of Law No. 10,639/03 by highlighting an educational process rooted in Black corporealities and experiences within emancipatory movements.